The cured [videorecording (DVD)] - Page, Elliot, 1987-; Keeley, Sam, 1990-; Vaughan-Lawlor, Tom (Shout! / Scream Factory, 2018)
What happens when the undead return to life? In a world ravaged by a virus that turns the infected into zombies, a cure is found and the wrenching process of reintegrating the survivors back into society begins. Among the formerly afflicted is Senan, a young man haunted by the horrific acts he committed while infected. He attempts to restart his life, but is society ready to forgive him and those like him? Or will fear and prejudice once again tear the world apart?